Placental Macrophage (Hofbauer Cell) Responses to Infection During Pregnancy: A Systematic Scoping Review - Fakonti, Georgia; Pantazi, Paschalia; Bokun, Vladimir; Holder, Beth (Frontiers in Immunology, 2022)
Background: Congenital infection of the fetus via trans-placental passage of pathogens can result in severe morbidity and mortality. Even without transmission to the fetus, infection of the placenta itself is associated with pregnancy complications including pregnancy loss and preterm birth. Placental macrophages, also termed Hofbauer cells (HBCs), are fetal-origin macrophages residing in the placenta that are likely involved in responding to placental infection and protection of the developing fetus. As HBCs are the only immune cell present in the villous placenta, they represent one of the final opportunities for control of infection and prevention of passage to the developing fetus. Objective and rationale: The objective of this review was to provide a systematic overview of the literature regarding HBC responses during infection in pregnancy, including responses to viral, bacterial, and parasitic pathogens. Methods: PubMed and Scopus were searched on May 20th, 2021, with no limit on publication date, to identify all papers that have studied placental macrophages/Hofbauer cells in the context of infection. The following search strategy was utilised: ((hofbauer* OR "hofbauer cells" OR "hofbauer cell" OR "placental macrophage" OR "placental macrophages") AND (infect* OR virus OR viral OR bacteri* OR parasite* OR pathogen* OR LPS OR "poly(i:c)" OR toxoplasm* OR microb* OR HIV)). Outcomes: 86 studies were identified for review. This included those that investigated HBCs in placentas from pregnancies complicated by maternal infection and in vitro studies investigating HBC responses to pathogens or Pathogen-Associated Molecular Patterns (PAMPs). HBCs can be infected by a variety of pathogens, and HBC hyperplasia was a common observation. HBCs respond to pathogen infection and PAMPs by altering their transcriptional, translational and secretion profiles. Co-culture investigations demonstrate that they can replicate and transmit pathogens to other cells. In other cases, they may eliminate the pathogen through a variety of mechanisms including phagocytosis, cytokine-mediated pathogen elimination, release of macrophage extracellular traps and HBC-antibody-mediated neutralization. HBC responses differ across gestation and may be influenced by pre-existing immunity. Clinical information, including gestational age at infection, gestational age of the samples, mode of sample collection and pregnancy outcome were missing for the majority of studies.